Cattle production in the Tropics. Volume 1, General introduction and breeds and breeding - Payne, W.J.A. (Longman, 1970)
The monograph consists of two parts. The first part give a geographic overview of the region including, the topography, climate and natural vegetation. The total number of cattle, their distribution and methods of utilisation in the region outlined. The second part deals with the origin of tropical and sub-tropical breeds. Detailed classification and descriptions of their origin, habitat, physical characteristic and utilities included. Breeding methods and fertility discussed in detail.